Identification and functional characterization of Toll-like receptor 2-1 in geese. - Yong, Yanhong.; Liu, Shaofeng.; Hua, Guohong.; Jia, Rumin.; Zhao, Yuntao.; Sun, Xingmin.; Liao, Ming.; Ju, Xianghong. (2016)
Background: Toll-like receptor 2 (TLR2), an important pattern recognition receptor, activates proinflammatory pathways in response to various pathogens. It has been reported in humans and chicken, but not in geese, an important waterfowl species in China. Since some vaccines stimulate robust immune responsesl in chicken but not in geeeses we speculated that their immune systems are different.; Keywords: Goose, TLR2-1, NF-кB, Mycoplasma, Salmonella, Infection.; Springer Open.